Comparison of Acute Physiological and Psychological Responses Between Moderate-Intensity Continuous Exercise and Three Regimes of High-Intensity Interval Training - Olney, Nicole; Wertz, Timothy; LaPorta, Zachary; Mora, Adam; Serbas, Jasmine; Astorino, Todd A (Journal of strength and conditioning research, 2018)
Olney, N, Wertz, T, LaPorta, Z, Mora, A, Serbas, J, and Astorino, TA. Comparison of acute physiological and psychological responses between moderate-intensity continuous exercise and three regimes of high intensity interval training. J Strength Cond Res 32(8): 2130-2138, 2018-High-intensity interval training (HIIT) elicits similar physiological adaptations as moderate-intensity continuous training (MICT) despite less time commitment. However, there is debate whether HIIT is more aversive than MICT. This study compared physiological and perceptual responses between MICT and 3 regimes of HIIT. Nineteen active adults (age = 24.0 ± 3.3 years) unfamiliar with HIIT initially performed ramp exercise to exhaustion to measure maximal oxygen uptake (V[Combining Dot Above]O2max) and determine workload for subsequent sessions, whose order was randomized. Sprint interval training (SIT) consisted of six 20-second bouts of "all-out" cycling at 140% of maximum watts (Wmax). Low-volume HIIT (HIITLV) and high-volume HIIT (HIITHV) consisted of eight 60-second bouts at 85% Wmax and six 2-minute bouts at 70% Wmax, respectively. Moderate-intensity continuous training consisted of 25 minutes at 40% Wmax. Across regimes, work was not matched. Heart rate (HR), V[Combining Dot Above]O2, blood lactate concentration (BLa), affect, and rating of perceived exertion (RPE) were assessed during exercise. Ten minutes postexercise, Physical Activity Enjoyment (PACES) was measured via a survey. Results revealed significantly higher (p ≤ 0.05) V[Combining Dot Above]O2, HR, BLa, and RPE in SIT, HIITLV, and HIITHV vs. MICT. Despite a decline in affect during exercise (p < 0.01) and significantly lower affect (p ≤ 0.05) during all HIIT regimes vs. MICT at 50, 75, and 100% of session duration, PACES was similar across regimes (p = 0.65), although it was higher in women (p = 0.03). Findings from healthy adults unaccustomed to interval training demonstrate that HIIT and SIT are perceived as enjoyable as MICT despite being more aversive.